Writing Learning Using Picture to Picture Method for Junior High School Students Procedure Text Material - Mulyadi Mulyadi; Delia Milla Vernia; Toto Widiarto; Fitria Hasanusi (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this study was to described the use of the Picture to picture method in the procedural text material for seventh grade students of SMP Kanzul Mubarok Bekasi. The population of this study was 80 people. The sample was 23 people. The research method used classroom action research (PTK). This study used two cycles. Before the 2 cycles were carried out, a pre-cycle was carried out to see the initial results of student learning outcomes in the procedure text material. Students were given procedural text material in English subjects using the picture to picture method for two meetings. At the initial meeting / cycle, an average of 74.7 was obtained and in the second session an average of 77. This indicated that this method could improve learning outcomes in English, the procedural techniques could improve learning outcomes for junior high school students.